Iterated Function Systems for Real-Time Image Synthesis - Nikiel, Slawomir (Springer London : Imprint: Springer, 2007)
Natural phenomena can be visually described with fractal-geometry methods, where iterative procedures rather than equations are used to model objects. With the development of better modelling algorithms, the efficiency of rendering, the realism of computer-generated scenes and the interactivity of visual stimuli are reaching astonishing levels. Iterated Function Systems for Real-Time Image Synthesis gives an explanation of iterated function systems and how to use them in generation of complex objects. Contents include: •Discussion of the most popular fractal models applied in the field of image synthesis. •Presentation of iterated function system models, including recent developments in IFS representation. •Exploration of algorithms for creating and manipulating fractal objects, and techniques for implementing the algorithms. •Use of practical examples to demonstrate the implementation and application of IFS models. The book contains both a description text and pseudo-code samples for the convenience of graphics application programmers. Slawomir Nikiel is an Assistant Professor at the Institute of Control and Computation Engineering, University of Zielona Góra. He started working with fractal geometry in 1995. His current research interests include fractal image synthesis for real-time computer graphics and virtual environments. The information in the book comes from the results of his recent research.